Excessive daytime sleepiness and its predictors among type 2 diabetes mellitus patients at central ethiopia - Alemayehu Wondie; Mitiku Mammo Taderegew; Betemariam Girma; Atsede Getawey; Zufan Tessema; Ambaw Abebaw Emrie; Tamene Fetene Terefe (Scientific Reports)
Abstract Excessive daytime sleepiness is a common finding among type 2 diabetes mellitus patients. However there is scarce data that shows the magnitude of excessive daytime sleepiness, & its association with type 2 diabetes mellitus. Hence, the study aimed to assess the prevalence of excessive daytime sleepiness and its associated factors among type 2 diabetes mellitus patients at Wolkite University Specialized Hospital. A Hospital-based cross-sectional study was employed from January 15 to March 15, 2022, among 229 Type 2 diabetes mellitus patients. Data was collected by semi-structured questionnaires, then entered into the Epi data version 4.6 and exported to SPSS version 25.0 for analysis. Binary and multiple logistic regression analysis was used to assess factors associated with excessive daytime sleepiness and statistical significance was set at P-value < 0.05. The prevalence of Excessive daytime sleepiness among type 2 diabetes mellitus was 27.1%. Age (AOR: 1.08; 95%CI: 1.03, 1.12), frequent snoring (AOR: 2.9; 95%CI: 1.24, 6.80), comorbid hypertension (AOR: 2.64; 95%CI: 1.17, 5.96), obesity (AOR: 2.7; 95%CI: 1.03, 7.13), and poor glycemic control (AOR: 6.68; 95%CI: 1.83, 24.41) were independently associated with Excessive daytime sleepiness among type 2 diabetes mellitus patients. Excessive daytime sleepiness was reported in more than a quarter of type 2 diabetes mellitus patients. Age, frequent snoring, hypertension, obesity, and poor glycemic control were significantly associated with Excessive daytime sleepiness among type 2 diabetes mellitus patients. Therefore health care providers should assess not only for how well their patients’ diabetes is controlled but also for excessive daytime sleepiness.